HOW SPEECH ACTS WORK IN TRANSLATION: AN ANALYSIS ON SPEECH ACTS TRANSLATING A SCRIPT OF TITANIC FILM - Arso Setyaji (Universitas Sebelas Maret, 2014)
The aim of this work is to know how speech acts work in translation. It is to find out an alternative definition of translation, to know the relationship between speech acts and types of translation, and to find the possibility that speech acts are able to influence the quality of translation. Through content analysis, it is found that translation is not only the process of meaning transference but also the process of intention transference from Source Language (SL) to target Language (TL). It is also found that speech acts are in relation to types of translation. When some utterances are translated with the idea of locutionary act, the tendancy of translation type belongs to literal translation. While some which are translated with the idea of illocutionary act, it belongs to idiomatic translation. And, it is possibly true that the action of ‗loss‘ and ‗gain‘ belongs to perlocutio nary acts. In relation to quality of translation, the use of locutionary act will perform the accuracy of meaning while that of illocutionary act will lead to naturalness or acceptability. And, the effect of illocutionary force will be realized into action by making ‗loss‘ and ‗gain‘; it will increase readabilit y.Keywords: locutionary, illocutionary, perlocutionary, literal, idiomatic, loss, gain